Vitamin D content in human breast milk: a 9-mo follow-up study. Issue 1 (16th December 2015) - við Streym, Susanna; Højskov, Carsten S; Møller, Ulla Kristine; Heickendorff, Lene; Vestergaard, Peter; Mosekilde, Leif; Rejnmark, Lars
ABSTRACT: Background: Parents are advised to avoid the direct sun exposure of their newborns. Therefore, the vitamin D status of exclusively breastfed newborns is entirely dependent on the supply of vitamin D from breast milk. Objectives: We explored concentrations of ergocalciferol (vitamin D2 ) and cholecalciferol (vitamin D3 ) (vitamin D) and 25-hydroxivitamin D2 plus D3 (25-hydroxyvitamin D [25(OH)D]) in foremilk and hindmilk during the first 9 mo of lactation and identified indexes of importance to the concentrations. Design: We collected blood and breast-milk samples from mothers at 2 wk ( n = 107), 4 mo, ( n = 90), and 9 mo ( n = 48) postpartum. Blood samples from infants were collected 4 and 9 mo after birth. We measured concentrations of vitamin D metabolites in blood and milk samples with the use of liquid chromatography–tandem mass spectrometry. Results: Concentrations of vitamin D and 25(OH)D correlated significantly and were higher in hindmilk than in foremilk. Milk concentrations were also correlated with maternal plasma 25(OH)D concentrations. In foremilk and hindmilk, concentrations were a median (IQR) of 1.35% (1.04–1.84%) and 2.10% (1.63–2.65%), respectively, of maternal plasma 25(OH)D concentrations ( P < 0.01). Milk concentrations showed a significant seasonal variation. Mothers who were taking vitamin D supplements had higher concentrations than did nonusers. Medians (IQRs) of infant daily intake through breast milk of vitamin D and 25(OH)D were 0.10 μg (0.02–0.40 μg) and 0.34 μg (0.24–0.47 μg), respectively, which were equal to a median (IQR) antirachitic activity of 77 IU/d (52–110 IU/d). Conclusions: The supply of vitamin D from breast milk is limited. Exclusively breastfed infants received <20% of the daily dose recommended by the Institute of Medicine for infants during the first year of life. This trial was registered at clinicaltrials.gov as NCT02548520.